Musical journeys : performing migration in twentieth-century music - Scheding, Florian, 1976- (The Boydell Press, 2019)
The displacement of European musics and musicians is a defining feature of twentieth-century music history.
Keywords: Music -- 20th century -- History and criticism.; Emigration and immigration.; Émigration et immigration.; Migration period (Medieval culture or period); emigration.; migrations (events); immigration.; MUSIC -- History & Criticism.; Emigration and immigration; Music; 1900-1999; Criticism, interpretation, etc.